Pengaruh Model Pembelajaran Permainan Tos Gambar terhadap Hasil Belajar Siswa pada Materi Mengenal Mata Uang dalam Pembelajaran IPS Kelas III di Madrasah Ibtidaiyah Nahdlatul Ulama Tanjung Mulia - Anni Latifah Nasution; Thessa Herdyana; Zon Saroha Ritonga (Medan Resource Center, 2025)
The mastery of currency concepts is essential in early social studies education, yet many primary school students struggle to understand these abstract ideas. This study investigates the effect of the Picture Slap game (Permainan Tos Gambar) on students’ learning outcomes in currency material at Grade III of MI Nahdlatul Ulama Tanjung Mulia. Employing a quantitative approach with a quasi-experimental pretest–posttest control group design, the study involved 24 students divided into an experimental class taught using the Picture Slap game and a control class taught using conventional methods. Data were collected through multiple-choice tests consisting of 20 pretest and 20 posttest items. The experimental class mean score increased from 64 to 88, while the control class improved from 61 to 82.5. An independent samples t-test confirmed a statistically significant difference in learning outcomes between both groups. N-Gain analysis further showed moderate effectiveness in the experimental class (56%) compared to a low category in the control class (44%). These findings indicate that the Picture Slap game positively and effectively enhances students’ learning outcomes in currency learning.